Adaptation of the Keirsey Temperament Sorter II (KTS-II) for the Chinese vocational university students majoring in preschool education - Masayu Binti Dzainudin, Tee Ying Qin (Tanjung Malim, 2024)
Adaptation of the Keirsey Temperament Sorter II (KTS-II) for the Chinese vocational university students majoring in preschool education by Masayu Binti Dzainudin, Tee Ying Qin